Adhesions in Non-Operatedabdomen: A Review of 150 Cases At A Private Hospital (Journal of Fatima Jinnah Medical University, 2018)
Objective: To observe the presence of intra-abdominal adhesion in previously non-operated abdomen. Design: A prospective observational study. Setting: The National Hospital and Medical Centre, Lahore. Patients: 150 patients were included in this study. Main outcome measures: Intra-abdominal adhesions were noted with the help of laparoscope. Results: There were 48 males and 102 females. Out of the 150 patients adhesions were seen to be present in 53 patients, the majority of whom were females. Conclusion: On the basis of our study we conclude that adhesions are present in a significant number of patients even with previously non-operated abdomen.
Keywords: Non-operated abdomen, Adhesions, laparoscopic.